Social Construction of Ideal Wife (Wife Material) in the Minangkabau Society in Nagari Lubuk Basung, Agam Regency - Indah Rovita, Nabilla; Rahman, Tyka (UIN Sjech M. Djamil Djambek Bukittinggi, 2025)
This research is motivated by an understanding of the obstacles to women's material well-being in society, especially in Nagari Lubuk Basung, Lubuk Basung District, Agam Regency, which is transforming in line with the times. This research aims to describe the social construction of wife material in Minagkabau society in Nagari Lubuk Basung District, Lubuk Basung, Agam Regency. The research method employed is qualitative research, utilizing qualitative descriptive methods. The informants in this research consist of 3 (three) involved informants, namely traditional leaders in the form of Niniak Mamak and Bundo Kanduang, as well as one of the community leaders, and the support of 5 (five) resident communities. In Nagari Lubuk Basung. The data collection method involves observation, interviews, and documentation. The data analysis method involves data reduction, data presentation, and conclusion. Meanwhile, data validity sources, techniques, and time. The research results show that the social construction of 'wife material' in Minangkabau, especially in Nagari Lubuk Basung, remains valued; society views women who possess good education, skills, and a career as being considered 'wife material'. A combination of domestic, educational, and career is considered the key to creating an ideal woman who not only plays a role in the family but can also contribute to society and advance the family economy.